Faktor-Faktor yang Berhubungan dengan Tingkat Kecemasan pada Pasien Preoperative di RS Mitra Husada Pringsewu - Diny Vellyana; Arena Lestari; Asri Rahmawati (Politeknik Kesehatan Tanjung Karang, 2017)
All of the nursing intervention in hospital was not certainly be positively accepted by patients. People ability has different, so that can arise the stress condition or anxiety. The prevalence of anxiety in America were more than 28%. The age who get anxiety were 9-17 years, 13% age of 18-54 years, 16% age of 55 and 11.4% of elderly. Women have risk to anxiety, two times than man. This study was to know the factors that related to anxiety level in Preoperative patient in Mitra Husada Hospital, Pringsewu, in 2016. The method of this study was a correlation with using cross sectional approach. The population were 58 respondents. Technique of sampling was using accidental sampling. Data were analyzed by univariat and bivariat using Chi square. The result showed that there were a relationship of gender, age, and economic status (p-value<0.05) and there were not a relationship of level of education variable (p-value>0.05) with the anxiety level of Preoperative patient in Mitra Husada Hospital, Pringsewu.